ABPN BILLING APPLICATION - Prashant S. Bhandare; Nilesh D. Kashid; Sankalp S. Salunkhe; Saurabh S. Salunke; Yasin S. Shaikh (International Journal of Innovations in Engineering Research and Technology, 2022)
This Android Application named ABPN Billing Application that is of important for Billing and invoicing of Audits.